Chronic neuropathic pain components in whiplash-associated disorders correlate with metabolite concentrations in the anterior cingulate and dorsolateral prefrontal cortex: a consensus-driven MRS re-examination - Pinilla-Fernández, Irene; Ríos-León, Marta; Deelchand, Dinesh Kumar; Garrido, Leoncio; Torres-Llacsa, Mabel; García-García, Fernando; Vidorreta, Marta; Ip, I. Betina; Bridge, Holly; Taylor, Julian; Barriga-Martín, Andrés (Frontiers in Medicine, 2024)
Introduction: Whiplash injury (WHI) is characterized by a forced neck flexion-extension, which frequently occurs after motor vehicle collisions. Previous studies characterizing differences in brain metabolite concentrations and correlations with neuropathic pain (NP) components with chronic whiplash-associated disorders (WAD) have been demonstrated in affective pain processing areas such as the anterior cingulate cortex (ACC). However, the detection of a difference in metabolite concentrations within these cortical areas with chronic WAD pain has been elusive. In this study, single voxel magnetic resonance spectroscopy (MRS), following the latest MRSinMRS consensus group guidelines, was performed in the anterior cingulate (ACC), left dorsolateral prefrontal (DLPFC), and occipital (OCC) cortex to quantify differences in metabolite concentrations for individuals with chronic WAD with or without neuropathic pain (NP) components. Materials and methods: Healthy individuals (n=29) and participants with chronic WAD (n=29) were screened with the Douleur Neuropathique 4 questionnaire (DN4) and divided into groups without (WAD-noNP, n=15) or with NP components (WAD-NP, n=14). Metabolites were quantified with LCModel following a single session in a 3T MRI scanner within the ACC, DLPFC and OCC. Results: Participants with WAD-NP presented moderate pain intensity and interference compared with the WAD-noNP group. MRS analysis demonstrated a higher glutamate concentration in the ACC and lower total choline (tCho) in the DLPFC in the WAD-NP group versus WAD-noNP group, with no intergroup metabolite difference detected in the OCC. Stepwise multiple regression revealed that the normalized ACC glutamate/total creatine (tCr) (P=0.01), DLPFC nacetyl-aspartate (NAA)/tCr (P=0.001), and DLPFC tCho/tCr levels (P=0.02) predicted NP components in the WAD-NP group (ACC r 2 =0.26, α=0.81; DLPFC r 2 =0.62, α=0.98). The normalized Glu/tCr concentration was higher in the healthy compared to the WAD-noNP group within the ACC (p<0.05), but not in the DLPFC nor OCC. Neither sex nor age affected key normalized metabolite concentrations related to WAD-NP components when compared to the WAD-noNP group. Discussion: This study demonstrates that elevated glutamate concentrations within the ACC is related to chronic WAD-NP components, while higher NAA and lower tCho metabolite levels suggest a role for increased neuronal-glial signaling and cell membrane dysfunction in individuals with chronic WAD NP components.